2021
DOI: 10.1002/glia.24032
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of aquaporin‐4 expression in the central nervous system investigated using M23‐AQP4 null mouse

Abstract: In astrocytes, unknown mechanisms regulate the expression of M1 and M23 isoforms of water channel aquaporin‐4 (M1‐AQP4 and M23‐AQP4). The ratio between these two isoforms controls the AQP4 assembly state in the plasma membrane known as orthogonal arrays of particles (OAPs). To give new insights into these mechanisms, here, we explore the regulation of AQP4 expression in the spinal cord of a CRISPR/Cas9 M23‐null mouse model (M23‐null). In the M23‐null spinal cord OAP assembly, the perivascular localization of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In addition to preferential adhesion to scaffolding proteins as a mechanism that enhances endfoot expression of AQP4 and especially the AQP4ext isoform, it has recently been reported that local translation of certain astrocyte proteins occurs in endfeet 42 . Regulatory proteins that direct translation of individual AQP4 isoforms have been discovered (see 43 ), raising the possibility that local translation may bias expression in specific cellular compartments. Combined with selective retention by cytoskeleton-linked scaffolds, this could lead to both stable and dynamic polarization of the endfoot to respond to local demands for water flux.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to preferential adhesion to scaffolding proteins as a mechanism that enhances endfoot expression of AQP4 and especially the AQP4ext isoform, it has recently been reported that local translation of certain astrocyte proteins occurs in endfeet 42 . Regulatory proteins that direct translation of individual AQP4 isoforms have been discovered (see 43 ), raising the possibility that local translation may bias expression in specific cellular compartments. Combined with selective retention by cytoskeleton-linked scaffolds, this could lead to both stable and dynamic polarization of the endfoot to respond to local demands for water flux.…”
Section: Discussionmentioning
confidence: 99%
“… 19 A better understanding of OAPs may be possible in the future with the development of a novel mouse lacking the OAP-forming AQP4-M23 isoform. 20 , 21 An AQP4 isoform (AQPex) has also been reported that has an extended carboxy-terminus containing a conserved perivascular localization signal generated by translational read-through. 22 , 23 The consequences of this carboxy-terminal extension are yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not explore the reason for decreased M1 isoform, the possible cause could be altered translational regulation by Rho-kinase. 48 Such altered ratio of M1 and M23 isoform might be important for the formation of water channels and regulation of edema.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not explore the reason for decreased M1 isoform, the possible cause could be altered translational regulation by Rho-kinase. 48 Such altered ratio of M1 and M23 isoform might be important for the formation of water channels and regulation of edema. After cerebral ischemia, activated microglia and astrocytes had been observed to take part in acute neuroinflammatory processes, and thereby neuronal cell death.…”
Section: Discussionmentioning
confidence: 99%